Theoretical Aspects of Professional Competence of Police Officers from the Tactical and Operative Response Unit - Ye. S. Romanenko (Law and Safety)
In this article the author has made a theoretical analysis of law enforcement officials’ professional competence and has defined the meaning of professional competence of the police officer in the tactical-operational respond unit (TOR) of the National Police of Ukraine. Taking into consideration specific official tasks and professional activity the author describes the main abilities of the police unit (TOR). Among the structural components of professional competence of the police unit TOR: personal, active, social competence is separated. It is shown the intentional filling of structural ingredients of the professional competence of the police unit TOR. It is underlined that the actuality of the research of the development of police officers’ professional competence in this tactical-operational respond unit is connected with the increasing of citizens’ “close” looks at the police actions on the whole and a new-organized unit of the patrol police especially.